VFR : the behaviour of 'balik kampung' traveller - Kasim, Yaziz (2007)
Travel involving 'balik kampung' can have a range of purpose. For example, the travel might be to highlight an event such as festivals and wedding. Alternatively, it might be an extra bonus if added to a vacation in a popular destination. In addition, individual mobility has increased in Malaysia, as car ownership has risen steadily, whilst incomes have generally risen steadily than the costs of running a car. However, little is known about Malaysia ‘balik kampung’ travellers, especially with regard to their travel behaviour. This study attempts to identify the behaviour of the ‘balik kampung’ traveller. To this point, all ‘balik kampung’ traveler have been based on the assumption of single-destination travel, i.e. when they leave home, they go directly to the destination and then return directly home. In many cases this assumption is incorrect. As shown in the study by Seaton and Tagg (1995), suggested that a trip to visit a friend or relative might be a combination of several trip types. Comparison of single and multi destination in terms of socio-demographic and trip characteristics is proposed to draw greater attention to the market’s importance in terms of its relative size and economic impact. This analysis should provide valuable information for several sectors of tourism including retailing, restaurants, car rental companies, and commercial accommodation.